A framework for online publishing in the University of Malaya - Abdul Ghani, N.; Suparjoh, S.; Hamid, S. (2008)
Scholarly communication activities such as journal publication and technical writings have been enhanced with the utilization of internet technology. Electronic publishing replaced the dissemination of knowledge findings through printed documents. The utilization of electronic publishing concept offers more advantages oiler the traditional way of communicating knowledge. This study identifies the online publishing technology and capabilities which could support the development of the online publishing system. This paper presents a proposed framework used for developing an Online Publishing in the University of Malaya (OPUM). This proposed framework, for OPUM system provides a platform and mechanism for the scholarly communities in UM to communicate within its societies in terms of sharing, extending, exchanging, promoting, debating and distributing their findings, ideas and knowledge via an online publishing system.